Multiple-Dose Safety, Tolerability, and Pharmacokinetics of Oral Nemonoxacin (TG-873870) in Healthy Volunteers - Chung, David T. (American Society for Microbiology (ASM), 2010)
Nemonoxacin (TG-873870) is a novel nonfluorinated quinolone with broad-spectrum activities against Gram-positive and Gram-negative aerobic, anaerobic, and atypical pathogens, as well as against methicillin-resistant Staphylococcus aureus, vancomycin-resistant S. aureus, and multiple-resistant bacterial pathogens. We conducted a randomized, double-blind, placebo-controlled, dose-escalating study to ascertain the safety, tolerability, and pharmacokinetics of nemonoxacin. We enrolled 46 healthy volunteers and used a once-daily oral-dosing range of 75 to 1,000 mg for 10 days. Additionally, the food effect was evaluated in subjects in the 500-mg cohort. Nemonoxacin was generally safe and well tolerated, with no significant changes in the clinical laboratory tests or electrocardiograms. Adverse effects, including headache, contact dermatitis, and rash, were mild and resolved spontaneously. Nemonoxacin was rapidly absorbed within 2 h postdosing, and generally, a steady state was reached after 3 days. The maximum plasma concentration and the area under the plasma concentration-time curve were dose proportional over the dosing range. The elimination half-life was approximately 7.5 h and 19.7 h on days 1 and 10, respectively. Approximately 37 to 58% of the drug was excreted in the urine. Food affected the pharmacokinetics, with decreases in the maximum plasma concentration and area under the plasma concentration-time curve of 46% and 27%, respectively. However, the free AUC/MIC(90) of nemonoxacin was more than 100 under both the fasting and fed conditions, predicting the efficacy of nemonoxacin against most of the tested pathogens. In conclusion, the results support further clinical investigation of once-daily nemonoxacin administration for antibiotic-sensitive and antibiotic-resistant bacterial infections.